Decision Support System in Service Satisfaction Assessment Using the Weighted Product (WP) Method at the New Equator Store - Ria Yestiva Rona; Indra Kanedi; Abdussalam Al Akbar (Jurnal Media Infotama, 2025)
In the era of increasingly fierce retail business competition, customer satisfaction is the key to success, but Toko New Khatulistiwa faces challenges in evaluating service satisfaction in a structured manner because it still relies on subjective manual methods. The main problem faced by the store is the absence of a structured customer satisfaction evaluation method, so that the assessment process becomes subjective and less accurate. This research aims to develop a decision support system (SPK) to assess customer service satisfaction at Toko New Khatulistiwa objectively and measurably. This research uses the Weighted Product (WP) method to perform calculations based on predetermined criteria, namely service quality, service speed, staff friendliness, place comfort, and price satisfaction. The system is built using PHP programming language and runs on a local server. The results showed that the WP method can produce accurate alternative rankings and help stores identify aspects of service that need to be improved. The implementation of this system is expected to improve service quality and customer loyalty.